2018
DOI: 10.1002/kpm.1564
|View full text |Cite
|
Sign up to set email alerts
|

Interfirm ties and knowledge transfer: The moderating role of absorptive capacity of managers

Abstract: Through the lens of social capital perspective, this paper assesses how individuals' interactions and their learning capabilities explain the transfer of good practices in an interorganizational network. Primary data were collected from export consortia in Tunisia through a questionnaire survey. The research underlines the impact of the strength and the range of ties between managers. It is also found that managers' absorptive capacity moderates the impact of the strength of ties. This study considers the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Hence, some research examines the role of the strength of ties on different variables, including innovation, knowledge transfer, and ACAP. For instance, Khachlouf and Quilin (2018) examine the association between a range of strength of ties in improving knowledge transfer among managers in Tunisia.…”
Section: Moderating Role Of the Strength Of Ties With Local Smesmentioning
confidence: 99%
“…Hence, some research examines the role of the strength of ties on different variables, including innovation, knowledge transfer, and ACAP. For instance, Khachlouf and Quilin (2018) examine the association between a range of strength of ties in improving knowledge transfer among managers in Tunisia.…”
Section: Moderating Role Of the Strength Of Ties With Local Smesmentioning
confidence: 99%
“…In light of this, it is conceivable that absorptive capacity enables the swift detection and exploitation of emergent insights for the benefit of entrepreneurial ventures. In an attempt to understand the possible intervening role of absorptive capacity, several studies (Aljanabi, 2018;Khachlouf and Quélin, 2018;Patel et al, 2015) employing absorptive capacity as an intervening variable, have reported its mixed effects on the relationship between different business-related concepts.…”
Section: Effectuation and Small Business Performancementioning
confidence: 99%
“…In general, the mechanism of previous interactions or collaborations implies that the frequency of collaborations between organizations strengthens the links and fosters higher levels of trust, closeness, and understanding [ 56 ]. Link strength, an important factor studied in collaborative networking and knowledge transfer, encompasses various elements such as time, emotional intensity, trust, and reciprocal services that characterize the relationship [ [57] , [58] , [59] , [60] ]. Increased trust, familiarity, and mutual understanding between organizations contribute to effective knowledge transfer and a greater willingness to commit to helping recipients understand new external knowledge [ 36 , 58 , 59 , 61 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%